A novel non-starch based cationic polymer as flocculant for harvesting microalgae. (January 2019) - Kumar, Niwas; Banerjee, Chiranjib; Kumar, Niraj; Jagadevan, Sheeja
Graphical abstract: Highlights: Three freshwater microalgal species isolated and identified by ITS sequence analysis. A novel non starch based cationic LBG polymer synthesized and characterized. CLBG was found to be a better flocculant than its pristine form. Using low dosage of CLBG high flocculation efficiency was achieved. Due to its natural origin the biodegradability issues were minimized. Abstract: This work intends towards the preparation of different grades of cationic locust bean gum biopolymer (CLBG) through the incorporation of 2, 3-epoxypropyltrimethylammonium chloride (GTMAC) on to the pristine locust bean gum (LBG) biopolymer. Among them the best grade was further selected, characterized and their flocculation efficacy was evaluated towards harvesting of three different indigenous isolated green microalgae viz . Chlorella sp. NCQ, Micractinium sp. NCS2 and Scenedesmus sp. CBIIT(ISM). Flocculation efficiency of 96.68%, 96.64%, and 97.42% were obtained for Chlorella sp. NCQ, Micractinium sp. NCS2 and Scenedesmus sp. CBIIT(ISM) at an optimum dosage of 55, 40, and 30 ppm respectively. Thus CLBG was proven to be an efficient flocculant towards harvesting of green microalgae than its natural form.